1994
DOI: 10.1161/01.atv.14.3.453
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure of cultured bovine endothelial cells to oxidized LDL abolishes prostacyclin release.

Abstract: We investigated the effect of chronic exposure (3 days) with low-density lipoprotein (LDL) and oxidized (Ox)-LDL on the unstimulated and stimulated formation of prostacyclin (6-keto-prostaglandin [PG]F, O ) and total inositol phosphates (IPs) by cultured bovine aortic endothelial cells. Neither basal nor bradykinin-stimulated (1 to 10 nmol/L) formation of 6-keto-PGF,,, was affected by LDL, except at the highest concentration of bradykinin tested (100 nmol/L). In the presence of the antioxidants N-acetyl-L-cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…3). The inhibition of agonist-stimulated PG!2 generation in our study is consistent with the observations reported by Thorin et al (1994) and may reflect inhibition of the cyclooxygenase pathway and/or receptor activation by histamine. Oxidized LDL and reactive oxygen species influence gene expression and activate nuclear transcription factors (see Andalibi, Liao, Imes, Fogelman & Lusis, 1993;Adcock, Brown, Kwon & Barnes, 1994;Lavrovsky, Schwartzmann, Levere, Kappas & Abraham, 1994;Ares, Kallin, Eriksson & Nilsson, 1995;and see Figs 1 and 3 in Brand, Page, WaIli, Neumeier & Baeuerle, 1997) involved in the expression of iNOS and the antioxidant stress protein haem oxygenase-1 (HO-1), which catalyses metabolism of haem to biliverdin/bilirubin and carbon monoxide (CO; see Maines, Mark & Ewing, 1993).…”
Section: Effects Of Low Density Lipoprotein On Endothelial Cell Prostsupporting
confidence: 93%
See 1 more Smart Citation
“…3). The inhibition of agonist-stimulated PG!2 generation in our study is consistent with the observations reported by Thorin et al (1994) and may reflect inhibition of the cyclooxygenase pathway and/or receptor activation by histamine. Oxidized LDL and reactive oxygen species influence gene expression and activate nuclear transcription factors (see Andalibi, Liao, Imes, Fogelman & Lusis, 1993;Adcock, Brown, Kwon & Barnes, 1994;Lavrovsky, Schwartzmann, Levere, Kappas & Abraham, 1994;Ares, Kallin, Eriksson & Nilsson, 1995;and see Figs 1 and 3 in Brand, Page, WaIli, Neumeier & Baeuerle, 1997) involved in the expression of iNOS and the antioxidant stress protein haem oxygenase-1 (HO-1), which catalyses metabolism of haem to biliverdin/bilirubin and carbon monoxide (CO; see Maines, Mark & Ewing, 1993).…”
Section: Effects Of Low Density Lipoprotein On Endothelial Cell Prostsupporting
confidence: 93%
“…Prolonged exposure (-3 days) of bovine aortic endothelial cells to oxidized LDL decreases basal and bradykinin-stimulated prostacyclin (PGI2) production (Thorin, Hamilton, Cominiczak & Reid, 1994). However, another study, using the same cell type, reported that native and oxidized glycated LDL increased basal PG!2 production (Kobayashi, Watanabe, Umeda, Taniguchi, Masakado, Yamauchi & Nawata, 1995).…”
Section: Effects Of Low Density Lipoprotein On Endothelial Cell Prostmentioning
confidence: 99%
“…Porcine aortic endothelial cells were isolated by enzymatic digestion using type II collagenase as described previously [36]. Cells were grown in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% foetal bovine serum, 1% penicillin-streptomycin, and glutamine.…”
Section: Isolation Of Endothelial Cellsmentioning
confidence: 99%
“…oxLDL is generated by auto-oxidation in the presence of transition metals (3,4), by cell-mediated mechanisms (5-7), and by enzyme-mediated mechanisms (8 -11). It induces the early changes of atherosclerosis: the expression of adhesion molecules on endothelial cells (12), a decrease in production of endothelial cell-derived relaxing factor (13) and prostacyclin (14), the transformation of macrophages and smooth muscle cells to foam cells (15), the production of various proinflammatory cytokines and growth factors by almost all vascular cells (16,17), the proliferation and migration of vascular cells (18 -20), the retardation of endothelial regeneration (21), and changes in the balance between procoagulant and anticoagulant activity on the vascular cell surface (22). These changes consequently trigger a series of cellular responses in the arterial wall that result in the formation of atheromatous lesions.…”
Section: Oxidized Low Density Lipoprotein (Oxldl)mentioning
confidence: 99%